Study the impact of clinical pharmacist provided patient counseling on hypertension management in rural Indian population - Katta Venkatesh Ramanath; Katti Ravi Venkappa (Archives of Global Professionals, 2013)
Objective: To assess the patient counseling provided by clinical pharmacist on hypertension management in a rural population. Materials and Methods: It is a prospective, randomized and interventional study conducted over a period of 9 months. The envelop randomization method was adopted to group the patients into control and intervention. Results: A total of 200 hypertensive patients were approached. Out of which 95 patients consented to participate and only 90 patients completed the study. Among these hypertensive patients, 65 were men and 25 women. The knowledge, attitude and practices (KAP) score at baseline was 47.76 ± 7.33 in control and 47.20 ± 5.82 in the intervention group, respectively. The same in the third follow-up was found to be 35.96 ± 3.54 in control and 31.56 ± 1.95 in the intervention group, respectively. The P values were 0.691 at the baseline, 0.060 in first follow-up, 0.001 in second follow-up, and < 0.001 in third follow-up. Mean score of various domains (recall, access, and regimen screens) to medication adherence showed a significant improvement. The P values of adherence to medication regimen at baseline and third follow-up was 0.974 and 0.329, respectively. The overall comparison of quality of life (QoL) scores showed a large improvement (suggestive significance) from baseline (P = 0.494) to final follow-up (P = 0.51). Conclusion: This study shows that the involvement of clinical pharmacists in rural hypertension management has a positive impact in creating awareness about the disease, drugs and its usage, and its effect on quality of life.